IKLAN LAYANAN MASYARAKAT GO GREEN MELALUI MEDIA POSTER - Abel Azonda, Dra. Jupriani, M.Sn, Drs. Suib Awrus, M.Pd (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
Have you ever imagined a world filled only by men only. Many animals are extinct(except animal parasites), as well as plants. It's a very terrible situation when the rain forestturned into deserts, rivers dry up and the sources of life dwindling. Humans as the onlyruler on earth grows like ants spend all the resources present and future. Living may only former planet called "Earth" was once blue now turns red. we as humans are the most perfect creature God created, as a rational creature, then it is our duty to preserve the survival of living beings on this earth. therefore I try to foster a sense of care for the environment through public service announcements in the media go green poster. Kata Kunci: Iklan Layanan Masyarakat, Go Green, Poster,Illegal Logging